The Confident Leader: How the Most Successful People Go from Effective to Exceptional - Kase, Larina (New York Tata Mcgraw Hill, 2008)
Many people who want to advance in their career or business are faced with an innate fear of change--even positive change that could move them forward. Using cutting-edge research to help readers become true leaders in their fields, Kase provides strategies to help readers move out of their comfort zones and better distinguish the positive decisions and actions that will dramatically propel their success. She includes interviews with top business thinkers such as Seth Godin, Joe Vitale, Annie McKee, and Tim Sanders.
Keywords: Leadership